Structural, surface, and theoretical investigation of hydrophobic-modified nanodiamond powders - Nazerke Kydyrbay; Mergen Zhazitov; Muhammad Abdullah; Tolagay Duisebayev; Yerbolat Tezekbay; Anuar Aldongarov; Mirat Karibayev; Nurxat Nuraje; Olzat Toktarbaiuly (Scientific Reports)
Abstract Nanodiamonds (NDs) have received much attention in science and technology due to their superior structural and functional characteristics. In this study, NDs were successfully functionalized with Triethoxy(octyl)silane (TREOS) to make them superhydrophobic. Surface functionalization was carried out through hydrolysis and condensation reactions to create stable Si–O–C and Si–O–Si bonds. Characterization techniques like Raman spectroscopy, XRD, SEM, FTIR, and water contact angle measurements confirmed the structural integrity and efficient functionalization of the functionalized NDs. The observed superhydrophobicity with a 151° contact angle is understandable based on both silane functionalization and nanoscale surface roughness. These observations suggest the prospects of TREOS-modified NDs for use in waterproof coatings, self-cleaning surfaces, and anti-corrosion materials. Furthermore, the excellent dispersion of hydrophobic NDs in nonpolar solvents reveals that they can be applied in lubrication and anti-wear. Future efforts would be the further improvement of ND surface modification and its application in practical products, e.g., protective coatings, biomedical devices, and high-performance nanocomposites.